Terrorism and counter-terrorism: ethics and liberal democracy - Miller, Seumas (Blackwell public philosophy, 2009)
The varieties of terrorism -- Defining terrorism -- Terrorism and collective responsibility -- Terrorism-as-crime -- Terrorism, war and states of emergency -- Torture -- Bioterrorism and the dual-use dilemma